Work-related hand injuries: type, location, cause, mechanism and severity in a tertiary hospital - Alhusuny, Ameer; Gyanchand Rampal, Lekhraj Rampal; Arumugam, Manohar; M. Y., Adon; Ariffin, Ahmad Azuhairi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2012)
Introduction: Work-Related Hand Injuries (WRHIs) may result in disability and diminished productivity and cause economic impacts not only to the individual, worker’s families and industries, but to the local community as well. Objectives: To determine the prevalence of severe Work-Related Hand Injuries (WRHIs) and factors associated at a tertiary hospital. Methods: A pre-tested validated questionnaire was used to obtain data. All patients 18 years and above with WRHIs seen at a tertiary hospital between January 2010 and June 2010 were included in the study. Data was analysed using SPSS version 18. Results: Out of the 297 industrial accidents, 74 (24.9%) were WRHIs. Among those with WRHIs, (47.3%) of them had severe hand injuries. The overall mean age of the respondents was 30.36 (± 9.54 SD) years. Majority (82.5%) of the injuries occurred between Mondays to Friday. Majority (70.1%) of hand injuries were caused by machine and 48.6% of the hand injuries occurred when the hand was caught in the operating part of the machine. Majority (62.1%) of the respondents had fingers’ injuries and 32.4% had open fracture. Bivariate analysis showed that there was significant association between severity of WRHIs and locations of injury, mechanisms of injury, sources of injury and sectors of industry (p < 0.05). Logistic regression analysis showed that WRHIs was significantly associated with source of injury and sector of industry. Respondents with hand injury resulted while operating on mechanical machine was 26 times more likely to report severe WRHIs than those with other sources of their hand injury like (sharp tool, heavy door, and wet floor). Respondents working in metal-machinery industries were eight times more likely to report severe WRHIs than those who working in other sectors of industry like (wood-furniture, constriction, food preparing, service and automotive). Conclusions: WRHIs contributed to 24.9% of all industrial accidents seen at the emergency department and orthopaedic clinic and 47.3% of the respondents with WRHIs had severe hand injuries. Severity of WRHIs was significantly associated with sources of injury and sectors of industry.